Should we consult Kant when assessing agent's moral responsibility for harm? - Klampfer, Friderik (2009)
The focus of the paper is the conditions under which an agent can be justifiably held responsible or liable for the harmful consequences of his or her actions. Kant has famously argued that as long as the agent fulfills his or her moral duty, he or she cannot be blamed for any potential harm that might result from his or her action, no matter how foreseeable these may (have) be(en). I call this the DutyAbsolves-Thesis or DA. I begin by stating the thesis in a more precise form and then go on to assess, one by one, several possible justifications for it: that (i) it wasn't the view Kant himself actually held or was committed to; (ii) there is nothing strange about the DA, either theoretically or intuitively; (iii) the DA is more plausible as an account of legal (either criminal or tort) liability; (iv) the DA becomes perfectIy plausible when conceived as a thesis about what insulates the agent from either remedial moral responsibility or the demands of compensatory justice; (v) the rationale for the DA is to protect our moral assessment of agents and their actions from the threat of moral luck. I show, using the famous Inquiring Murderer example, all these (and some other) justificatory attempts unsuccessful. I conclude that besides being counter-intuitive, the DA-thesis also lacks firm theoretical grounding and should therefore be rejected as (part of) an account of outcome moral responsibility.
Bibliografija: str. 156.
Abstract.
Keywords: filozofija -- Kant -- moralna odgovornost -- laži -- dobrohotna laž -- dolžnost -- škoda -- slabo; philosophy -- Kant -- benevolent lies -- moral responsibility -- duty -- harm -- wrong -- moral luck